RADIKALISME DAN FUNDAMENTALISME AGAMA DI ERA REFORMASI - I Gede wardana (Journal Social and Humaniora, 2017)
Reform in Indonesia opened a space of freedom and openness. In an atmosphere of openness began to look advocates enforcement of Islamic law. The enforcement of Islamic law that, among other figures of Islamic movements such as DI / TII NII, which is a very radical return to Indonesia from exile. To enforce Islamic law, they began a radical movements and fundamentalism in the country, without any meaningful control of state institutions and laws. While on the other hand, emerging global developments in the situation which led religious groups do a movement supporting religious issues. This situation cause collisions culture in Indonesia. This paper will discuss radicalism and fundamentalism in Indonesia after the reform. Keywords: The issue of religious radicalism and fundamentalism